Home-Based Enterprise and Its Impediment Factors to Self-Help House Improvement in Kampong Cikini, Jakarta - Joko Adianto; Rossa Turpuk Gabe (Department of Architecture Universitas Muhammadiyah Jakarta, 2020)
This research aims to embellish the existing literature on Home-Based Enterprise (HBE) to recuperate it as one of the effective solutions for self-help slum improvement programs in the future. Many experts have praised HBE as one of the plausible solutions for slum alleviation through income-generating activities that will enable the underprivileged to perform self-help house improvement. However, there is a vague establishment between HBE to self-help house improvement in Kampong Cikini, as one of the notable slum settlements in Central Jakarta. Through the employment of the case study method, this research established HBE’s contribution to self-help house improvement is less significant because of several impediments, which indicates the increment monthly income from HBE cannot automatically ignite the self-help house improvement. Both HBE and self-help house improvement are inseparable from socio-economy activities in the neighborhood and cannot be comprehended as an individual economy household’s activities. Therefore, specific solutions are required to overcome the mainly encountered impediments with considering the established interwoven domestic and economic activities, for increasing the impact of HBE to self-help house improvement.